Young Adults’ Selection and Use of Dependent Coverage under the Affordable Care Act - Chen, Weiwei (Frontiers in Public Health, 2018)
The dependent coverage expansion under the Affordable Care Act (ACA) required health insurance policies that cover dependents to offer coverage for policyholder’ children up to age 26. It has been well documented that the provision successfully reduced the uninsured rate among the young adults. However, less is known about whether dependent coverage crowded out other insurance types and whether young adults used dependent coverage as a fill-in-the-gap short-term option. Using data from the Survey of Income and Program Participation 2008 Panel, the paper assesses dependent coverage uptake and duration before and after the ACA provision among young adults aged 19–26 versus those aged 27–30. Regressions for additional coverage outcomes were also performed to estimate the crowd-out rate. It was found that the ACA provision had a significant positive impact on dependent coverage uptake and duration. The estimated crowd-out rate ranges from 27 to 42%, depending on the definition. Most dependent coverage enrollees used the coverage for 1 or 2 years. Differences in dependent coverage uptake and duration remained among racial groups. Less healthy individuals were also less likely to make use of dependent coverage.